Consumer Behavior of Non-Muslim Costumer Post Communal Conflict (1999-2000) in Bank Syariah Indonesia branch Tobelo North Halmahera - Umasugi, Nirwan; Quilim, Cici Aryansi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The inter-religious conflicts between Islam and Christianity (1999-2000) in North Halmahera had negative impact on the community such a destructive impression. The existence of Bank Syariah Indonesia branch Tobelo as part of the manifestation of Islamic law, has its own challenges in dealing with psychological trauma for non-Muslims. However, Bank Syariah Indonesia branch Tobelo still a special attraction as the number of customers has increased every year and shows the behavioral change of non-Muslim. The research aims to analyze the factors of consumer behavior such as profit sharing, business factor, social factors and personal factors influence the customer decisions in choosing to save at Bank Syariah Indonesia branch Tobelo after the 1999-2000 Communal Conflict. Through the multiple regression linear by SPSS ver.22, the author tries to find out the effect of profit sharing, business factor, social factor, and personal factor towards the interest of non-Muslim costumer. The result shows there is 70.9% of simultaneously effect towards the interest of non-Muslim costumer, meanwhile partially just business factor which has not shown any effect towards interest of non-Muslim costumer.